Speaking of sex workers: How suppression of research has distorted the United States' domestic HIV response. Issue 45 (May 2015) - Forbes, Anna
Abstract Sex workers remain a vulnerable population at risk for HIV acquisition and transmission. Research suggests that interventions at the individual level, such as condom distribution, are less effective in preventing HIV among sex workers than structural changes such as allowing safer work settings and reducing the harassment and abuse of sex workers by clients and police. In the US, HIV incidence has not declined in the last decade. This may be due in part to its policy of wilful ignorance about sex work, but the data to resolve the question simply do not exist. Political actions such as PEPFAR's prostitution pledge and a congressional campaign against "waste, fraud and abuse" in research are products of an ideological environment that suppresses research on HIV prevention and treatment needs of sex workers. Even basic prevalence data are missing because there is no "sex worker" category in the US National HIV Behavior Surveillance System. However, international efforts are taking a public health approach and are calling for decriminalization of sex work, as the most effective public health strategy for reducing HIV incidence among sex workers. Although such an approach is not yet politically feasible in the US, some urgent practical policy changes can be implemented to improve data collection and generation of evidence to support HIV prevention and treatment programs targeting sex workers.